The Future of Post-human Urban Planning. A Preface to A New Theory of Density, Void, and Sustainability - BAOFU, Peter (Cambridge Scholars Publishing, 2009)
The Future of Post-human Urban Planning. A Preface to New theory of Density, void, ....